2018
DOI: 10.3126/ajms.v9i1.18505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepcidin as a biomarker for the differential diagnosis of iron deficiency anaemia and anaemia of chronic disease

Abstract: Background:Anaemia affects approximately 1.62 billion people globally corresponding to 24.8% of the world's population. Iron deficiency anaemia (IDA) and anaemia of chronic disease (ACD) are the most common forms of anaemia. A hormone produced by the liver, hepcidin, is the primary regulator of iron homeostasis and its production increases in ACD and decreases in IDA. Usually, ACD and IDA coexist and sometimes look identical on peripheral blood smears. Aims and Objectives: The current study aims to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(20 reference statements)
2
3
0
Order By: Relevance
“…Our results revealed that in a group of anemic and nonanemic RA patients, HEP is correlated (to varying magnitudes) to markers anemia, iron metabolism, inflammation, and erythropoiesis ( Table 1 ). This is in accordance with previous studies demonstrating similar associations between HEP and anemia markers 21 22 23 24 25 or iron metabolism 25 26 27 28 29 however, others have reported no correlation. 23 30 31 32 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results revealed that in a group of anemic and nonanemic RA patients, HEP is correlated (to varying magnitudes) to markers anemia, iron metabolism, inflammation, and erythropoiesis ( Table 1 ). This is in accordance with previous studies demonstrating similar associations between HEP and anemia markers 21 22 23 24 25 or iron metabolism 25 26 27 28 29 however, others have reported no correlation. 23 30 31 32 …”
Section: Discussionsupporting
confidence: 93%
“…demonstrating similar associations between HEP and anemia markers [21][22][23][24][25] or iron metabolism [25][26][27][28][29] however, others have reported no correlation. 23,[30][31][32] In order to better understand the dynamics of this complex correlation matrix, we performed data reduction using PCA where linear combinations of the original variables were "reduced" to single factors.…”
Section: Discussionmentioning
confidence: 96%
“…We found excellent diagnostic properties for hepcidin-25, FRT, TSAT, and MCV for distinguishing IDA from ACD in ESRD patients. We presented the best diagnostic characteristic at 9.32 ng/mL for hepcidin-25 which is consistent with literature data [ 17 , 26 , 29 ]. Valenti et al have stated that an adequate iron balance was likely present in most patients included in the second and third hepcidin quartiles (1.56–49.8 ng/mL) [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Patients that have been examined in this study lacked a rare homozygous variant HFE C282Y A/A and HFE H63D G/G. Several previous studies have reported that the prevalence of the homozygosity for HFE C282Y and HFE H63D mutations is very low in Southern and Eastern Europe [ 29 , 41 43 ]. It is well-known that these variants are a common cause of hereditary hemochromatosis, and patients included in this study did not have this disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation